Recurrent gastric antral vascular ectasia: a single center experience - Cavallaro, Andrea; Zanghì, Antonio; Di Vita, Maria; Catania, Vito Emanuele; Longo, Giovanni; Lo Menzo, Emanuele; Granata, Roberta; Valenti, Maria Rosaria; Cappellani, Alessandro; Di Majo, Simone (Frontiers in Surgery, 2024)
Gastric Antral Vascular Ectasia (GAVE) is an uncommon cause of chronic or acute gastrointestinal bleeding and accounts for approximately 4% of the upper gastrointestinal bleedings. This disease is often associated with systemic diseases such as liver cirrhosis, chronic kidney failure, autoimmune conditions, diabetes mellitus, hypothyroidism and cardiovascular diseases. However the etiopathogenesis remains controversial. We retrospectively reviewed the cases of Gastric Antral Vascular Ectasia treated at our Digestive Surgery Unit. A total of 9 patients were identified with Male/Female ratio of 1,25:1, and an average age of 75.51 years (SD±9.85). All patients underwent endoscopic Argon Plasma Coagulation(APC)treatment. At the time of the review, data on eight patients was available at 36 months follow up. Argon Plasma Coagulation appear to be safe and effective for hemostasis of bleeding vascular ectasia. Only one (11.1%) patient was treated surgically because of hemodynamic instability after multiple unsuccessful endoscopic treatments. No intraoperative and postoperative complication or bleeding relapse was experienced. Based on our data, we concluded that endoscopic Argon Plasma Coagulation is technically simple, but requires multiple re-intervention secondary to the incidence of relapses. Further larger randomized studies should be conducted to assess the role of elective surgery as first intervention in stable patients with severe pathology, and the timing of surgery after failed endoscopic treatment.